Emotional intelligence among nursing students of a government campus in eastern Nepal - Shrestha, Melina; Mandal, Punam Kumari (Journal of Kathmandu Medical College, 2021)
Background: Emotional intelligence is the ability to recognise one’s own feelings and those of others, for motivating ourselves, and for managing emotions well in ourselves and others. It is important to identify the level of emotional intelligence among nursing students for effective nursing leadership and quality nursing care.Objective: To assess the level of emotional intelligence of nursing students.Methods: A cross-sectional, descriptive research design was used to assess the level of emotional intelligence among 132 nursing students at Biratnagar Nursing Campus, Nepal. Data were collected by census method using self-administered structured questionnaire from 2018-05-13 to 2018-05-27. Emotional intelligence was measured using the Schutte Self Report Emotional Intelligence Test. Descriptive and inferential statistics (Chi-square test) was analysed to find out the association between emotional intelligence and demographic variables.Results: The findings showed that 96 (72.7%) of the respondents were from the 15 to 18 years age group. Similarly, 104 (78.8%) of the respondents had joined nursing education by their own choice. This study showed the majority 108 (81.8%) had a high level of emotional intelligence and 24 (18.2%) had a moderate level of emotional intelligence. There was no association between student’s level of emotional intelligence and their demographic variables.Conclusion: The participating nursing students had high levels of emotional intelligence. Owing to growing complexity in the healthcare environment and increasing expectations of clients in today’s competitive health care marketplace, the nursing students should be provided with emotional intelligence training and concepts should be incorporated into the nursing curriculum.